A combined analysis of TyG index, SII index, and SIRI index: positive association with CHD risk and coronary atherosclerosis severity in patients with NAFLD - Dong, Wenyuan; Gong, Yuxin; Zhao, Jianqi; Wang, Yanan; Li, Bao; Yang, Youdong (Frontiers in Endocrinology, 2024)
Background: Insulin resistance(IR) and inflammation have been regarded as common potential mechanisms in coronary heart disease (CHD) and non-alcoholic fatty liver disease (NAFLD).Triglyceride-glucose (TyG) index is a novel biomarker of insulin resistance, System immuneinflammation index(SII) and Systemic inflammation response index(SIRI) are novel biomarkers of inflammation,these biomarkers have not been studied in CHD with NAFLD patients. This study investigated the correlation between the TyG index, SII index, and SIRI index and CHD risk among NAFLD patients.